PEMBERDAYAAN PETANI MELALUI PENGOLAHAN LIMBAH JERAMI PADI MENJADI PUPUK BOKASHI UNTUK TANAMAN PADI (Oryza sativa L.) - Dea Marini; Muhammad Tassim Billah; Yul Harry Bahar (Sekolah Tinggi Pariwisata Mataram, 2020)
Indonesia is an agricultural country with a majority in rice farming. Every year there is an increase in rice production resulting in an increase in the amount of agricultural waste such as straw. The habits of farmers in Cimalaka Subdistrict, which are burning straw to reduce agricultural waste, have a negative impact on the environment. The content of the elements in straw can be reused for rice plants and can increase soil fertility, therefore a study was carried out under the heading